Genome-wide analysis of mutations induced by carbon ion beam irradiation in cotton - Liu, Jianguang; Zhao, Guiyuan; Geng, Jinpeng; Geng, Zhao; Dou, Haikuan; Liu, Xu; An, Zetong; Zhang, Hanshuang; Wang, Yongqiang (Frontiers in Plant Science, 2023)
Carbon ion beam (CIB) irradiation is a powerful way to create mutations in animals, plants, and microbes. Research on the mutagenic effects and molecular mechanisms of radiation is an important and multidisciplinary issue. However, the effect of carbon ion radiation on cotton is uncertain. In this study, five different upland cotton varieties and five CIB doses were used to identify the suitable irradiation dose for cotton. Three mutagenized progeny cotton lines from the wild-type Ji172 were re-sequenced. The effect of half-lethal dose on mutation induction indicated that 200 Gy with LETmax of 226.9 KeV/μm was the most effective heavy-ion dose for upland cotton and a total of 2,959-4,049 single-base substitutions (SBSs) and 610-947 insertion-deletion polymorphisms (InDels) were identified among the three mutants by resequencing. The ratio of transition to transversion in the three mutants ranged from 2.16 to 2.24. Among transversion events, G:C>C:G was significantly less common than three other types of mutations (A:T>C:G, A:T>T:A, and G:C>T:A). The proportions of six types of mutations were very similar in each mutant. The distributions of identified SBSs and InDels were similar with unevenly distributed across the genome and chromosomes. Some chromosomes had significantly more SBSs than others, and there were “hotspot” mutation regions at the ends of chromosomes. Overall, our study revealed a profile of cotton mutations caused by CIB irradiation, and these data could provide valuable information for cotton mutation breeding.